The effects of joint design, bolting procedure and load eccentricity on fatigue failure characteristics of high-strength steel bolts. (April 2021) - Abdul Jawwad, Abdul Kareem; ALShabatat, Nabeel; Mahdi, Mofid
Highlights: FEM was used successfully to accurately model bolt loading under eccentricity. Thread runout is a strong potential failure location when it coincides with flange interface. Load eccentricity can result in high loads even at near-zero bolt pretention. Fatigue crack front curvature is related to the degree of axial misalignment between crack front ends. Stress concentration factor at thread is inversely related to the amount of eccentricity. Abstract: A detailed failure analysis was applied to a set of broken high-strength steel bolts originally fitted on a heavy fuel oil meter. The investigation included both experimental and numerical analysis. Experimental analysis confirmed failure of the bolts by a premature fatigue fracture process with failure being predominantly at thread runout. The present failure was prompted by the presence of relatively high stresses within the bolts – sometimes exceeding the material's yield strength. A two-stage finite element modelling (FEM) was used to model loading patterns within the overall meter assembly and also on individual bolts. FEM results have shown that loading patterns and the associated tensile stresses within bolts are the result of varying degrees of loading eccentricity, which itself was found to be the result of a neglectful bolting procedure. Furthermore, failure location is confirmed to be the result of a major design weakness where thread runout was found to coincide with flange interface. Contrary to some published results, fatigue crack front curvature was shown by experimental evidence to be related to the degree of axial misalignment between crack front ends rather than mean stress level. FEM results indicated that stress concentration factor is inversely related to the degree of load eccentricity and to a much lesser degree to the applied load. Finally, some operating and design recommendations are made in the light of present results as preventive measure of such failures in the future.